2012
DOI: 10.1136/heartjnl-2011-301107
|View full text |Cite
|
Sign up to set email alerts
|

Does additional linear ablation after circumferential pulmonary vein isolation improve clinical outcome in patients with paroxysmal atrial fibrillation? Prospective randomised study

Abstract: ObjectiveCircumferential pulmonary vein isolation (CPVI) has been considered the cornerstone of radiofrequency catheter ablation (RFCA) for atrial fibrillation (AF). However, it is unclear whether linear ablation in addition to CPVI improves clinical outcome.DesignProspective randomised study to compare the efficacy of CPVI and CPVI with additional linear ablation in patients with paroxysmal AF (PAF).SettingUniversity hospital.PatientsThis study enrolled 156 patients (male 76.3%, 55.8±11.5 years old (mean±SD))… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 30 publications
1
53
0
1
Order By: Relevance
“…To our knowledge, only 2 other randomized studies have evaluated the effect of linear ablation at the LA roof, with conflicting results . Hocini et al .…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 2 other randomized studies have evaluated the effect of linear ablation at the LA roof, with conflicting results . Hocini et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, circumferential antral PV isolation, particularly if it is combined with additional modification of AF substrate, whether by the linear LA ablation and/or CFAE ablation, may lead to the occurrence of atrial tachycardia in 7.6%-44% of patients [24,42,54,[194][195][196]. After usage of similar ablative strategy (CFAE + PVI), post-procedural incidence of atrial tachycardia was remarkably higher after the ablation of persistent AF than after the ablation of paroxysmal AF (20.0% vs. 2.4%) [197].…”
Section: Phrenic Nerve Injurymentioning
confidence: 99%
“…There are three basic strategies for modification of AF substrate: LA defragmentation by ablation of the complex fragmented atrial electrograms (CFAE), linear ablation of LA and ganglionated plexi ablation [3,[21][22][23][24][25][26][27][28][29]. CFAE are the electrograms during AF which have short cycle length (<120ms) or which are fractionated into two or more components, or show continuous atrial electrical activation [50].…”
Section: Figure 2 Catheter Ablation Of Paroxysmal Af: Elimination Ofmentioning
confidence: 99%
“…Late recurrences (defined as 6–12 months following the initial AF ablation procedure) was associated with PV reconnection in all patients, while very late recurrences (>12 months after the procedure) were associated with non-PV triggers in 85.7% of cases. The added benefit of performing additional linear ablation lines after PV isolation on improving outcomes following AF ablation has been further questioned in a prospective, randomised study of 156 patients with paroxysmal AF who were randomly assigned to undergo PV isolation only, PV isolation and a roof line, or PV isolation, roof line and a posterior inferior line 35. The investigators found no improvement in clinical outcome in the patients who received the additional lines while, unsurprisingly, the addition of the linear ablations significantly prolonged procedure times.…”
Section: Atrial Fibrillationmentioning
confidence: 99%